2015
DOI: 10.3758/s13414-015-0901-x
|View full text |Cite
|
Sign up to set email alerts
|

Sports can protect dynamic visual acuity from aging: A study with young and older judo and karate martial arts athletes

Abstract: A major topic of current research in aging has been to investigate ways to promote healthy aging and neuroplasticity in order to counteract perceptual and cognitive declines. The aim of the present study was to investigate the benefits of intensive, sustained judo and karate martial arts training in young and older athletes and nonathletes of the same age for attenuating age-related dynamic visual acuity (DVA) decline. As a target, we used a moving stimulus similar to a Landolt ring that moved horizontally, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 82 publications
1
37
0
2
Order By: Relevance
“…Specifically, findings from experiment 2 showed that active older adults performed the motion sense and position sense tests better than their non-active peers, supporting the view that active lifestyle has a positive effect on information processing and processing speed (e.g., Muions and Ballesteros 2014;Muions et al 2015;Voelcker-Rehage et al 2011). Noteworthy, significant differences in performance of the sensory tests between active and non-active older adults were observed under situations where those individuals had to evaluate motion/position in shorter time windows (i.e., for the 0.5°/s speed condition in the motion sense task and the 6°/s speed condition in the position sense task) or had to distinguish between false and true wrist movements during the motion sense task (i.e., in the sham condition).…”
Section: Discussionmentioning
confidence: 60%
“…Specifically, findings from experiment 2 showed that active older adults performed the motion sense and position sense tests better than their non-active peers, supporting the view that active lifestyle has a positive effect on information processing and processing speed (e.g., Muions and Ballesteros 2014;Muions et al 2015;Voelcker-Rehage et al 2011). Noteworthy, significant differences in performance of the sensory tests between active and non-active older adults were observed under situations where those individuals had to evaluate motion/position in shorter time windows (i.e., for the 0.5°/s speed condition in the motion sense task and the 6°/s speed condition in the position sense task) or had to distinguish between false and true wrist movements during the motion sense task (i.e., in the sham condition).…”
Section: Discussionmentioning
confidence: 60%
“…Some researchers and clinicians have hypothesised that dynamic visual acuity is related to athletic performance . There is currently no ‘gold standard’ for the evaluation of dynamic visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Martial arts such as Kung Fu, Judo, Karate or Taekwondo have also been shown to improve cognitive domains in older adults including postural control (Krampe et al, 2014), visual-spatial attention (Muiños and Ballesteros, 2014), dynamic visual acuity (Muiños and Ballesteros, 2015) as well as working memory and information processing speed (Pons van Dijk et al, 2013).…”
Section: Sport Tai Chi and Martial Arts As Interventionsmentioning
confidence: 99%